Investigation-Based Scientific Collaborative (IBSC) Learning Model to Foster Students’ Communication and Collaboration Skills - Manurung, Sri Hariani; Nasution, Marah Doly (Indonesian Journal of Education and Mathematical Science, 2026)
The development of communication and collaboration skills constitutes a critical demand in 21st-century learning. However, classroom practices remain predominantly teacher-centered, limiting students’ opportunities to actively engage in scientific investigation and collaborative work. This study aims to examine the effectiveness of the Investigation-Based Scientific Collaborative (IBSC) learning model in enhancing students’ communication and collaboration skills.This research employed a quasi-experimental design involving students as research participants. The experimental group received instruction using the IBSC model, while the control group was taught using conventional methods. Data were collected through assessment instruments measuring communication and collaboration skills, observation sheets, and supporting documentation. Data analysis was conducted using descriptive and inferential statistics to determine differences between the two groups.The findings indicate that students taught using the IBSC model demonstrate significantly higher communication and collaboration skills compared to those taught through conventional learning. The IBSC model promotes active student engagement in investigative activities, scientific discussions, and collaborative problem-solving, thereby positively influencing their ability to communicate and work effectively in teams.This study concludes that the Investigation-Based Scientific Collaborative (IBSC) learning model is effective as an alternative instructional approach for developing students’ communication and collaboration skills.